Impact of Low Level Laser Therapy on Mandibular Range Motion in Temporomandibular Joint Disorder in Iraqi Patients - Haidar Flayyih Hasan; Layla M. H. Al-ameri; Ammar Saleh Alalawi (Iraqi Journal of Laser, 2024)
Background: Temporomandibular disorder (TMD) is a painful condition that specifically affects the muscles, bones, and temporomandibular joint (TMJ). Pain can vary in intensity, ranging from mild to moderate or severe. It is often accompanied by limited movement of the jaw, resulting in a restriction of mouth opening. Aim of the study: The purpose of this study was to determine the effect of low-level laser therapy on mandibular range of motion in patients with temporomandibular joint disorders. Patients and methods: fifteen patients were randomly selected. The mandibular range of motion was evaluated for each patient before treatment and after 3 months, a dual-wavelength (810-980nm) diode laser was used in this study. Three main criteria were utilized in the statistical calculation, they are relaxed mouth opening, full mouth opening, and lateral mandibular movement. Paired t-test and one-way analysis of variance (ANOVA) tests were used for statistical analysis. Results: The study revealed a significant enhancement in mandibular range of motion in TMD patients during a short period of laser sessions. Conclusion: Low-level laser therapy is an efficient way to improve the mandibular range of motion in patients with temporomandibular joint disorder.